2017
DOI: 10.18632/oncotarget.19306
|View full text |Cite
|
Sign up to set email alerts
|

The ketogenic diet is not feasible as a therapy in a CD-1 nu/nu mouse model of renal cell carcinoma with features of Stauffer's syndrome

Abstract: The ketogenic diet (KD), a high-fat low-carbohydrate diet, has shown some efficacy in the treatment of certain types of tumors such as brain tumors and neuroblastoma. These tumors are characterized by the Warburg effect. Because renal cell carcinoma (RCC) presents similar energetic features as neuroblastoma, KD might also be effective in the treatment of RCC. To test this, we established xenografts with RCC 786-O cells in CD-1 nu/nu mice and then randomized them to a control diet or to KDs with different trigl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
4
1

Relationship

4
5

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 78 publications
0
21
0
Order By: Relevance
“…LCT-MCT8 diet significantly increased the concentration of blood ketone bodies in the mice already after five days of treatment (for breast cancer bearing mice see Supplementary Figure S1c; for healthy mice see Supplementary Figure S1d in [42]). In contrast, average blood glucose levels did not show any diet specific change and remained mostly unchanged until termination of the experiment after 80 days (Supplementary Figure S1d).…”
Section: Resultsmentioning
confidence: 99%
“…LCT-MCT8 diet significantly increased the concentration of blood ketone bodies in the mice already after five days of treatment (for breast cancer bearing mice see Supplementary Figure S1c; for healthy mice see Supplementary Figure S1d in [42]). In contrast, average blood glucose levels did not show any diet specific change and remained mostly unchanged until termination of the experiment after 80 days (Supplementary Figure S1d).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, Liśkiewicz et al also observed that long-term KD (79% fat content) increased renal tumor growth in a rat model of Tuberous Sclerosis [ 73 ]. Furthermore, we recently reported that KD is not feasible as a therapy in a CD-1 nu/nu mouse model of renal cell carcinoma with features of Stauffer’s syndrome [ 74 ]. Therefore, it is of utmost importance to evaluate the effect of KDs in preclinical studies on specific types of tumors and also to take into account the different genetic alterations before considering clinical studies, as differences in the response of tumor growth to dietary intervention between mice and humans cannot be excluded.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to the safe application of KDs reported in various cancer models, our research group recently reported that mice bearing renal cell carcinoma xenografts and with signs of Stauffer’s syndrome experienced dramatic weight loss and liver dysfunction when treated with a KD [ 4 ]. Another study investigating the effect of long-term KD treatment on kidney cancer described a pro-tumor effect of the KD in a rat model of tuberous sclerosis complex [ 5 ].…”
mentioning
confidence: 99%